Development of "Xiaohua Online" an apps in Mandarin language classroom: a pilot study / Loh Siaw San, Jenny Yap Tze Kie and Ngien Ming Ming - Loh, Siaw San; Yap, Jenny Tze Kie; Ngien, Ming Ming (Akademi Pengajian Bahasa, Universiti Teknologi MARA, 2023)
Traditional methods of language learning have certain limitations. Through the development of game applications, learners' memory can be deepened, and their interest and motivation can be stimulated to improve their learning efficiency. The researcher applied a literature review, app review and questionnaire. The subjects of the research consist- ed of non-Chinese Mandarin learners. After review, learners wanted to have an app based on the course syllabus. Every currently available program is geared toward the practice approach. In addition, the language medium that is used in the apps is most commonly English, and the researchers have not come across any Chinese learning programs that include the Malay language as an attached component. Games applications based on stories can help to increase learners' interest in learning, and the process of progressing through levels can make learning both challenging and interesting. An application with additional Malay annotations can make the software more valuable and convenient for Mandarin learner who had mastered Malay. Thus, researchers came up with the concept of "Xiaohua Online" to address this issue. "Xiaohua Online", is an online game for beginners in Mandarin. Using the search for a scattered map of Sarawak as the main thread of the game, it integrates the learning content from the UiTM Mandarin course. Based on a systematic and well-developed game curriculum, as well as targeted tests, it is hoped that it can breaks through the constraints of time and space, thus enhance learners' sense of achievement and motivation.